Made in the U.S.A. - Letts, Billie (New York : Grand Central Pub., 2008)
"Billie Letts takes readers on an unforgettable journey through the best and worst of America's heartland as she tells a story of two abandoned children desperately searching for people to call family and a place to call home"--Provided by publisher.
Keywords: Abandoned children -- Fiction; Middle West -- Fiction